A Novel Transient Current Limiter Based on Three-Phase Thyristor Bridge for Y-yg Transformers - Alok Kumar Shrivastav; Pradip Kumar Sadhu; Ankur Ganguly; Nitai Pal (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The transformer in flux current may be a transient current that happens in electrical devices has been charged. This current depends on completely different parameters probably the voltage magnitude, the switching on angle the permanent flux, the core physical phemeon characteristics, the primary circuit resistance, etc. To beat the issues arising owing to transients, these are required to be suppressed.In this paper, an easy and economical techniquie is conferred to limit the transient current of the Y-yg transformers. One amongst the most benefit of this technique is it doesn’t would like any negative feedback circuit or activity unit. The tactic relies on a three-phase thyristors bridge single LC reactor with the individual phases of electrical device. Since the amount of thyristors is reduced, the voltage ripple, electrical losses and therefore the malfunction likelihood due to device failure is reduced significantly. The projected technique has been simulated by MATLAB simulation. It’s shown that the projected style is a lot of economical for the transient current limitation of Y-yg transformers.